Motivating the Younger Generation in Reading: Integrating Technology in Understanding Digital Literacy - Nurman Samehuni Gea; Upaya Bakti Murni Gulo; Arozatulo Bawamenewi; Wenti Marlina Gulo (International Journal of Educatio Elementaria and Psychologia, 2024)
Reading is an important activity to develop insight, knowledge and critical thinking skills. Therefore, schools should organize literacy activities to increase interest in reading. Digital literacy is the ability to understand and use information from various digital sources and use technology and information from digital devices in various situations. The aim of this research is to develop an effective strategy for integrating technology in literacy promotion, to motivate the digital generation to read. The research technique is a qualitative method, with a case study approach, the research subjects are the digital generation, such as pupils, students and active social media users. The research object is the reading motivation of the digital generation and the integration of technology in the promotion of digital literacy. Assessment instruments (level of interest in reading, responsiveness, initiative to use technology in reading, and participation). The data collection techniques used are participant observation sheets to observe how the digital generation uses technology in reading, and document analysis to study existing digital literacy programs and how they integrate technology.